Q: 3 x - 4

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

okay if x-4=3 then x=7 bcause 4+3=x = 4+3=7 and 7-4=3!

(x - 3)/(12 - 4x) = (x - 3)/[4(3 - x)] = (x - 3)/[-4(x - 3)] = 1/-4 = -(1/4)

3 x 2 x 4 = 24 (3 x 2) x 4 = 6 x 4 = 24 3 x (2 x 4) = 3 x 8 = 24 2 x (3 x 4) = 2 x 12 = 24

No, multiplication is associative. 5 x (4 x 3) = 4 x (5 x 3) = 3 x (5 x 4) = 5 x 4 x 3 = 60

-1

Related questions

okay if x-4=3 then x=7 bcause 4+3=x = 4+3=7 and 7-4=3!

(x - 3)/(12 - 4x) = (x - 3)/[4(3 - x)] = (x - 3)/[-4(x - 3)] = 1/-4 = -(1/4)

x^(-5/3) = 4 1/x^(5/3) = 4 x^(5/3) = 1/4 [x^(5/3)]^(3/5) = (1/4)^(3/5) x = 1/4^(3/5) or, x = 4^(-3/5) Check: x^(-5/3) = 4 [4^(-3/5)]^(-5/3) = 4 ? 4 ^(15/15) = 4 ? 4^1 = 4 ? 4 = 4

x/3 + x = 4 times all by 3 x +3x = 12 add the two x's together 4x=12 divide by 4 x=3 test your work 3/3 + 3 =4 1+3=4 4=4

( 3/4 ) x ( 3/4 ) = ( 3 x 3 ) / ( 4 x 4 ) = 9/16

3 x 2 x 4 = 24 (3 x 2) x 4 = 6 x 4 = 24 3 x (2 x 4) = 3 x 8 = 24 2 x (3 x 4) = 2 x 12 = 24

972 4*9*9*3 4*81*3 4*243 =972

x^2 -x -12 / (x - 4) Factor ise the top line (x + 3)(x - 4) / (x - 4) Cancel down by 'x-4' Hence x + 3 is the answer!!!!

One solution is 8 x (4 - 3/3) = 8 x (4 - 1) = 8 x 3 = 24 And another, 8 x 3 x (4 - 3) = 8 x 3 x 1 = 24 And a third, (3 + 3) x ( 8 - 4) = 6 x 4 = 24

X=4/3

No, multiplication is associative. 5 x (4 x 3) = 4 x (5 x 3) = 3 x (5 x 4) = 5 x 4 x 3 = 60

x-2 and x -7?